2020
DOI: 10.1097/aln.0000000000003324
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Function of Estrogen Receptors in the Rodent Anterior Cingulate Cortex in Pain-related Aversion

Abstract: Background Brain-derived estrogen is implicated in pain-related aversion; however, which estrogen receptors mediate this effect remains unclear. This study hypothesized that the different estrogen receptors in the rostral anterior cingulate cortex play distinct roles in pain-related aversion. Methods Formalin-induced conditioned place avoidance and place escape/avoidance paradigms were used to evaluate pain-related aversion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…The deletion of the ER subunit α (ERα) in TRPV1 nociceptors abolishes IL-23- and IL-17-induced pain in females [ 48 ]. ER-β and G protein-coupled ER-1, but not ER-α, in the rostral anterior cingulate cortex are involved in pain-related aversion by modulating N -methyl- d -aspartate receptor-mediated excitatory synaptic transmission [ 49 ]. Behavioural tests revealed that the PWMT and PWCD peaked on the fifth day and lasted > 14 days in SNI animals.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of the ER subunit α (ERα) in TRPV1 nociceptors abolishes IL-23- and IL-17-induced pain in females [ 48 ]. ER-β and G protein-coupled ER-1, but not ER-α, in the rostral anterior cingulate cortex are involved in pain-related aversion by modulating N -methyl- d -aspartate receptor-mediated excitatory synaptic transmission [ 49 ]. Behavioural tests revealed that the PWMT and PWCD peaked on the fifth day and lasted > 14 days in SNI animals.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Some studies have shown that estrogen and its nuclear receptors (ERα and ERβ) play a critical role in pain regulation. 17 , 18 , 19 , 20 However, few reports have directly investigated estrogenic effects on the descending pain modulation system, especially the function of GPER in the RVM on the chronification of postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, 2016;Rossetti et al, 2016;Woolley & McEwen, 1993). In addition, membrane-associated estrogen receptors can induce rapid effects on synaptic function through multiple mechanisms involving ERα (Huang & Woolley, 2012), ERβ (Kramár et al, 2009;Zang et al, 2020), and GPER1 receptors (Kumar et al, 2015;Lebesgue et al, 2010). Here, in slices from ovariectomized rats that received subdermal implants to maintain E2 at levels similar to estrus (Quinlan et al, 2008), we found that the 20-min application of 10 nM E2 resulted in an increase in the amplitude of field EPSPs in the entorhinal cortex in vitro that was reversed following washout in normal ACSF.…”
Section: Discussionmentioning
confidence: 99%